Höpüpü: surfing stoked on the waves of Peniche. The surfer and the satisfaction with his surf tourism experience - Nunes, J.M. (2022)
More recently, surf has acquired an overwhelming dimension, both in terms of media coverage and in terms of economic relevance and direct impact in the communities. The Portuguese situation is a clear reflection of that, especially in Peniche, where this phenomenon is part of strategic documentation related with the “Sea economy”, namely via the so called “Surf Tourism”. Nowadays, Portugal is referred to as one of the most attractive countries as a tourist destination as a whole, but also as a tourist destination of reference when it comes to surfing. Furthermore, Peniche is one of the key locations for these activities, with an increasing range of packages and surf tourism offers, especially taking advantage of their environment, landscape and other characteristics related to nature. The main purpose of this work is to characterize in detail the “surfer/surf tourist” at Peniche and measure his satisfaction with this site as a surf tourism destination. In addition, it is proposed to the “surfer/surf tourist” to evaluate the satisfaction versus the level and quality of surf found. In order to achieve this purpose, a comprehensive survey was produced and conducted. The target was visitors of Peniche that matched to the typical “surfer/surf tourist”, achieving a response rate of 363 individuals. The results obtained and the knowledge produced as an outcome of this investigation lead us to build the profile of the “surfer/surf tourist” visiting Peniche in association with his expectative. Also, the study allowed leveraging policies and strategies directly addressing the expectations of this particular market niche in order to – using a sustainable approach – maximizing the potential of this activity.